Prediction of the seismic time-lapse signal of CO2/CH4 injection into a depleted gas reservoir - Otway Project - Caspari, Eva; Ennis-King, J.; Pevzner, Roman; Gurevich, Boris (CSIRO, 2012)
Stage I of the Otway project conducted by the Cooperative Research Centre for Greenhouse Gas Technologies (CO2CRC) in 2007-2010 included injection of 66000 tons of CO2-rich gas into a depleted gas reservoir at Naylor field, Otway Basin, Victoria. In this paper we present a seismic modelling study that estimates the time lapse response of CO2/CH4 injection into the Waarre C reservoir. Based on the static geological model, acoustic impedance inversion of the seismic baseline data as well as log data, two models with different levels of detail in the reservoir properties are built. The distribution of the injected CO2/CH4 mixture in the reservoir and the gas properties are obtained from flow simulations. In order to predict the change in acoustic impedance after injection, we employed the Gassmann fluid substitution workflow. The modelled total differences in acoustic impedance for different amounts of CO2/CH4 injected are of the same order of magnitude for both models and reflect the CO2 mass fractions predicted by flow simulations. Finally zero incidence synthetic data are computed for these cases using a statistical wavelet of the baseline data. The computed synthetics are compared to surface seismic and VSP monitoring data. The repeatability of the surface seismic data is too low to detect the predicted signal. For the 3D VSP data, the time-lapse signal/noise has a similar order of magnitude as the predicted signal. It may have the level required to detect the signal.